Address by YAB Tun Dr.Ismail Al Haj,Deputy Prime Minister Of Malaysia to members Of German Association for foreign policy at Adenauerallee 133,Bonn , on Thursday 9th December , 1971 at 6.00 pm. - Al haj, Ismail (1971)
I am deeply honoured to have been invited to address this distinguished gathering in Bonn, the capital of a powerful and friendly country which, no less than mine, is preoccupied with the supreme and urgent tasks of strengthening cooperation and reducing tensions between nations.